PERTUMBUHAN STEK PUCUK JABON PUTIH (Anthocephalus cadamba (Roxb.) Miq.) DENGAN PERENDAMAN MENGGUNAKAN EKSTRAK KECAMBAH KACANG HIJAU (Vigna radiata) - Huda, Nurul; Mukarlina, Mukarlina; Wardoyo, Elvi Rusmiyanto Pancaning (Jurnal Protobiont, 2019)
White jabon (Anthocephalus cadamba (Roxb.) Miq) are plants with high economic value. It can be propagated vegetatively using its shoot cuttings. One of the way to enhance the growth of shoot cuttings by submersion in green bean sprout extract was expected to produce shoot cuttings with better growth. This study aimed to determine the submersion effect of white jabon (A. cadamba) shoot cuttings in green bean (Vigna sinensis) sprout extract. The Completely Randomized Design (CRD) consisted of 5 levels of treatment were used. The cuttings were submerged in extract concentrations of 0%, 25%, 50%, 75%, and 100%. The study parameters of number of roots and leaves, plant height, wet and dry weight were observed. The results showed that the concentration treatment with 75% green bean sprout extract produced 9,25±2,50 root strands, 5,75±0,50 leaves, plant height of 20,13±1,11 cm, wet weight of 12,39±3,62 g, and dry weight of 1,51±0,42 g.